Pelatihan Microsoft Office Dalam Pembuatan Modul Ajar Bagi Guru SD Swasta Bani Adam AS - Siregar, Yunita Sari; Sembiring, Boni Oktaviana; Damanik, Almerinda Regina Puspa Sari (Jurnal Pengabdian Masyarakat, 2025)
This Microsoft Office training program aims to enhance the ability of teachers at Bani Adam AS Private Elementary School in developing effective and engaging digital teaching modules. The training was conducted through a hands-on approach, covering material on text processing using Microsoft Word and the use of PowerPoint as the primary medium for preparing instructional content. Evaluation was carried out through pre-tests and post-tests, as well as observation of participants’ work. The results of the training showed a significant improvement in teachers’ understanding and skills in designing teaching modules that are more interactive, well-structured, and aligned with the curriculum. Furthermore, the training encouraged teachers to be more creative in presenting technology-based learning materials, thereby improving the quality of classroom instruction.  The positive impact of this activity serves as a strong foundation for organizing follow-up training programs to further expand teachers’ proficiency in using digital technologies in education.